1997
DOI: 10.1097/00004424-199705000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Lactate (+lipid) Concentration in Brain Tumors with In Vivo Hydrogen Magnetic Resonance Spectroscopy During Radiotherapy

Abstract: Assessment of r-Lac(+lip) may adjunctively contribute to the early prediction of the radiotherapeutic effect on brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…The limited number of cases in their series could be an explanation for this difference between our and their data. From a structural point of view, astrocytomas are characterized by an occasional increase in the amount of Lip referable to the increased cellularity of the tumor and the relative increase of the membranous structures [14,35,49]. Although Lip are fairly nonspecific and nonreproducible markers [14,28], a finding confirmed by our data in this series, further studies are needed for the better understanding of this metabolite and its role in the astrocytomas' biochemical profile.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The limited number of cases in their series could be an explanation for this difference between our and their data. From a structural point of view, astrocytomas are characterized by an occasional increase in the amount of Lip referable to the increased cellularity of the tumor and the relative increase of the membranous structures [14,35,49]. Although Lip are fairly nonspecific and nonreproducible markers [14,28], a finding confirmed by our data in this series, further studies are needed for the better understanding of this metabolite and its role in the astrocytomas' biochemical profile.…”
Section: Discussionsupporting
confidence: 59%
“…In the future, new techniques such as three-dimensional chemical shift imaging as well as the technical ability to access quite small and discrete voxels suggest that continued progress should be possible using this modality. Indeed, even on a contemporary basis, MRS appears to be able to furnish useful information about the neoplastic aggressiveness of a particular lesion and may prove useful in evaluating the effectiveness of varying radio-therapeutic or chemotherapeutic treatment protocols [30,49] as well as in differentiating between local tumor recurrence and post-radiation necrosis, a very confounding and frequently encountered clinical dilemma [48,50]. Potentially, this noninvasive diagnostic modality could place a pre-operative histologic diagnosis of an intracranial tumor, which will be confirmed by the classical pathology examination and postoperatively will allow a real time analysis of the tumor's response to any adjunctive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…larity of the tumor and the relative increase in the membranous structures [17,21,33]. Although lipids are fairly non-specific and non-reproducible markers [10], further studies are needed for the better understanding of this metabolite and its role in the biochemical profile of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance spectroscopic (MRS) analysis offers many potential advantages in real-time analysis of intracranial neoplasms [19,22,24,31,33,34]. Recent evidence suggests that this maturing diagnostic modality with its ability to differentiate neoplastic cell types and their metabolic characteristics, as well as their malignant propensity, may assume an increasingly important role in everyday clinical practice [2,4,6,9,13,16,21,30,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that shrinkage of malignant cerebral lymphomas during irradiation is associated with a decrease of Cho and Lac and an increase in NAA, which precede reduction of the lesion volume [12][13][14] . Serial investigations of gliomas during and after chemotherapy 15,16 , radiotherapy 13,17-21 , brachytherapy 22 and SRS 23,24 consistently demonstrated that tumor shrinkage or stabilization of its growth is typically accompanied by a decrease of Cho content.…”
Section: Discussionmentioning
confidence: 99%